2010
DOI: 10.1038/emboj.2009.412
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and spatio-temporal features of protein aggregation in Escherichia coli and consequences on protein quality control and cellular ageing

Abstract: The aggregation of proteins as a result of intrinsic or environmental stress may be cytoprotective, but is also linked to pathophysiological states and cellular ageing. We analysed the principles of aggregate formation and the cellular strategies to cope with aggregates in Escherichia coli using fluorescence microscopy of thermolabile reporters, EM tomography and mathematical modelling. Misfolded proteins deposited at the cell poles lead to selective re-localization of the DnaK/DnaJ/ClpB disaggregating chapero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
390
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 266 publications
(421 citation statements)
references
References 38 publications
25
390
3
3
Order By: Relevance
“…However, there are also reports stating that exclusion of aggregates from mid-cell to the pole is energy-free, and simply results from nucleoid exclusion [17,20,[28][29][30]. Restriction of aggregates to the pole was also observed during treatment with substances disrupting the protein motive force, suggesting an energy independent process of aggregation [20]. Energy-independent polar localization was also confirmed by others [30] but also convincing opposite results were obtained [15].…”
Section: Cellular Formation Of Ibssupporting
confidence: 57%
See 4 more Smart Citations
“…However, there are also reports stating that exclusion of aggregates from mid-cell to the pole is energy-free, and simply results from nucleoid exclusion [17,20,[28][29][30]. Restriction of aggregates to the pole was also observed during treatment with substances disrupting the protein motive force, suggesting an energy independent process of aggregation [20]. Energy-independent polar localization was also confirmed by others [30] but also convincing opposite results were obtained [15].…”
Section: Cellular Formation Of Ibssupporting
confidence: 57%
“…There are claims that transport of aggregates to the poles is energy-driven as studies on reassembly of pressure dissociated IBs revealed that confinement to the pole is caused by the presence of the nucleoid but reassembly of smaller aggregates into large IBs does not occur in energy and nutrient depleted cells [16]. However, there are also reports stating that exclusion of aggregates from mid-cell to the pole is energy-free, and simply results from nucleoid exclusion [17,20,[28][29][30]. Restriction of aggregates to the pole was also observed during treatment with substances disrupting the protein motive force, suggesting an energy independent process of aggregation [20].…”
Section: Cellular Formation Of Ibsmentioning
confidence: 99%
See 3 more Smart Citations